Anthelmintic Activity of Hygrophila difformis Blume - Samanta, Krishanu; Hossain, Emdad; Pal, Dilip Kumar (Journal of Buffalo Science, 2012)
This study evaluated the anthelmintic activity of the petroleum ether, benzene, chloroform, ethanol extracts of aerial parts of Hygrophila difformis (Family: Acanthaceae). The Pheretima posthuma were used for all the experimental protocol due to their anatomical and physiological resemblance with the intestinal roundworms of ruminants and human beings. The worms were treated with the extract solutions containing three different concentrations (10, 25 and 30 mg/ml), for each extracts supplemented with 1% gum acacia in normal saline at 37 ± 1°C. Albendazole at a dose of 10 mg/ml was used as reference. The effectiveness of the extracts was judged on the basis of the loss of spontaneous movement and/or death of the worms. Qualitative phytochemical analysis of different extracts of the plant was carried out following the standard procedure. All extracts at different dose levels effectively paralyzed and killed the worm in dose-dependent fashion (p < 0.001). Maximum anthelmintic activity was found with benzene extract. Cardiac glycosides, tannins, steroids, flavonoids and saponins were found positive in phytochemical analysis. The present study established the anthelmintic activity of H. difformis and can be utilized for the ruminants.